Septic shock caused by Salmonella: still drawing attention - Varela Alcaraz, Alex Tomas (2025)
Salmonella infection is uncommon, but carries a high mortality rate if the patient developshemodynamic instability. It predominantly affects children and the elderly. The mechanismsby which nontyphoidal Salmonella causes urinary tract infection are generally attributed tohematogenous spread resulting from gastroenteritis or to the introduction of fecal microbiotathrough the urethra. In this case, the patient presented with a clinical picture characterized bythe onset of watery stools accompanied by emesis and followed by urinary symptoms.The presented clinical features prompted the development of this case report, which aims toprovide guidance in identifying risk factors and clinical manifestations that may raise suspicion ofSalmonella as the etiology. The patient had a history of acute gastroenteritis, after which urinarysymptoms and septic shock developed. The bacillus was isolated in both blood and urine culturesand was found to be sensitive to ciprofloxacin, the first-line antibiotic due to its intracellularactivity. This case underscores the importance of rational antibiotic use in the light of theemergence of beta-lactamase-producing Salmonella in Paraguay.This case report is noteworthy due to the infrequency of urinary tract infections with septic shockcaused by Salmonella. In this context, it is important not only to know the clinical syndromes thatmay be attributed to this bacillus, but also to highlight the patient’s socioeconomic background,since the infection is associated with the consumption of contaminated liquid or food.